2020
DOI: 10.1021/acs.jmedchem.0c00156
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Heparanase Activity: Tuning Sulfation Pattern and Glycosidic Linkage of Oligosaccharides

Abstract: Heparanase cleaves polymeric heparan sulfate (HS) molecules into smaller oligosaccharides, allowing for release of angiogenic growth factors promoting tumor development and autoreactive immune cells to reach the insulin-producing β cells. Interaction of heparanase with HS chains is regulated by specific substrate sulfation sequences. We have synthesized eleven trisaccharides that are highly tunable in structure and sulfation pattern, allowing us to determine how heparanase recognizes HS substrate and selects a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 78 publications
(215 reference statements)
0
23
0
Order By: Relevance
“…Sulfatases are a family of enzymes that mediate the selective removal of sulfate groups from HS chains [ 26 ]. Two heparanases mediate the cleavage of specific carbohydrate linkages, thus releasing fragments of the HS chain [ 31 ]. Individuals with type I diabetes exhibit high levels of heparanases activity resulting in poorly sulfated HS associated with β-cells [ 32 ].…”
Section: Sulfation Of Heparan Sulfates and Its Role In Adipose Tissuesmentioning
confidence: 99%
See 3 more Smart Citations
“…Sulfatases are a family of enzymes that mediate the selective removal of sulfate groups from HS chains [ 26 ]. Two heparanases mediate the cleavage of specific carbohydrate linkages, thus releasing fragments of the HS chain [ 31 ]. Individuals with type I diabetes exhibit high levels of heparanases activity resulting in poorly sulfated HS associated with β-cells [ 32 ].…”
Section: Sulfation Of Heparan Sulfates and Its Role In Adipose Tissuesmentioning
confidence: 99%
“…Additionally, elevated glucose activates inflammatory cells resulting in inflamed adipose tissues characteristic of obese individuals. These enzymes become important in diabetic individuals as the size and sulfation of HS are modified by glucose levels [ 31 ]. The HS-modifying enzymes found in adipose tissues are the same as found elsewhere; however, it is possible that their regulation is modified.…”
Section: Sulfation Of Heparan Sulfates and Its Role In Adipose Tissuesmentioning
confidence: 99%
See 2 more Smart Citations
“…The methodology will make it possible to prepare panels of compounds for structure−activity relationship studies to better understand the biology of heparan sulfate. A recent paper demonstrated that trifluoromethylphenyl-methanimine can also be employed to make HS oligosaccharides to modulate heparanase activity, 61 which is an enzyme that can remodel HS and has been implicated in cancer. The microarray data highlight key requirements of chemokines to engage with HS.…”
Section: ■ Conclusionmentioning
confidence: 99%